On New Space of Vector-Valued Generalized Bounded Sequences Defined on Product Normed Space - Pokharel, Jagat Krishna; Pahari , Narayan Prasad; Ghimire, Jhavi Lal (Nepal Journal of Mathematical Sciences, 2023)
Abstract available on the PDF.